2010
DOI: 10.1111/j.1365-2796.2010.02257.x
|View full text |Cite
|
Sign up to set email alerts
|

Potential CYP2C9‐mediated drug–drug interactions in hospitalized type 2 diabetes mellitus patients treated with the sulphonylureas glibenclamide, glimepiride or glipizide

Abstract: Abstract. Tirkkonen T, Heikkilä P, Huupponen R, Laine K (University of Turku; Turku University Hospital; and StatFinn Ltd; Turku, Finland). Potential CYP2C9-mediated drug-drug interactions in hospitalized type 2 diabetes mellitus patients treated with the sulphonylureas glibenclamide, glimepiride or glipizide. J Intern Med 2010; 268: 359-366.Objectives. Sulphonylureas are widely used in the treatment of type 2 diabetes mellitus (T2DM). Based on laboratory findings, we determined the clinical significance of po… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
24
0
2

Year Published

2012
2012
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 35 publications
(27 citation statements)
references
References 16 publications
0
24
0
2
Order By: Relevance
“…As with other sulphonylureas, the use of glimepiride in patients with type 2 diabetes is associated with an increased risk of hypoglycaemia [13]. Glimepiride is extensively metabolised in the liver, mainly by CYP2C9 [14], and concomitant administration of agents that inhibit CYP2C9, such as gemfibrozil and fluconazole, has been shown to increase the risk of hypoglycaemia [15]. Empagliflozin does not inhibit CYP450 enzymes in vitro (unpublished data), so the potential for CYP-mediated drug interactions is unlikely, but cannot be ruled out.…”
Section: Methodsmentioning
confidence: 99%
“…As with other sulphonylureas, the use of glimepiride in patients with type 2 diabetes is associated with an increased risk of hypoglycaemia [13]. Glimepiride is extensively metabolised in the liver, mainly by CYP2C9 [14], and concomitant administration of agents that inhibit CYP2C9, such as gemfibrozil and fluconazole, has been shown to increase the risk of hypoglycaemia [15]. Empagliflozin does not inhibit CYP450 enzymes in vitro (unpublished data), so the potential for CYP-mediated drug interactions is unlikely, but cannot be ruled out.…”
Section: Methodsmentioning
confidence: 99%
“…Beta blockers can mask the early warning symptoms of hypoglycemia; however, later studies have shown that these effects may be less prominent with newer beta-1 selective drugs [Shorr et al 1997]. As mentioned earlier, many antimicrobials present a high interaction risk with antidiabetics, especially with Sulfonylureas [Tirkkonen et al 2010, Parekh et al 2014. Interactions with antimicrobials are clinically most relevant because adverse effects take place most often whenever a drug is added or removed [Patsalos et al 2003], and antimicrobials are usually taken temporarily.…”
Section: Drugs Affecting the Efficacy Of Antidiabetic Agents In Generalmentioning
confidence: 99%
“…Thus, interactions due to CYP2C9 inhibition play a crucial role in the treatment with SUs. A Finnish study revealed that a clinically relevant interaction occurred in about 20% of T2DM patients treated with SUs; 75% of the identified interactions were due to concomitant treatment with trimethoprim, metronidazole, or ketoconazole [Tirkkonen et al 2010].…”
Section: Susmentioning
confidence: 99%
“…We started from a relatively low dose (200 mg daily) of oral FCZ because we already prescribed topical FCZ and due to concerns of a possible drug interaction between FCZ and glimepiride, an antidiabetic medication that was used in this patient 2223. The stroma infiltration soon subsided and the epithelium healed in 8 days.…”
Section: Discussionmentioning
confidence: 99%